Lipid-mRNA Nanoparticle Designed to Enhance Intracellular Delivery Mediated by Shock Waves - Zhang, J; Shrivastava, S; Cleveland, R; Rabbitts, T (American Chemical Society, 2019)
Cellular membranes are, in general, impermeable to macromolecules (herein referred to as macrodrugs, e.g., recombinant protein, expression plasmids, or mRNA), which is a major barrier for clinical translation of macrodrug-based therapies. Encapsulation of macromolecules in lipid nanoparticles (LNPs) can protect the therapeutic agent during transport through the body and facilitate the intracellular delivery via a fusion-based pathway. Furthermore, designing LNPs responsive to stimuli can make their delivery more localized, thus limiting the side effects. However, the principles and criteria for designing such nanoparticles remain unclear. We show that the thermodynamic state of the lipid membrane of the nanoparticle is a key design principle for acoustically responsive fusogenic nanoparticles. We have optimized a cationic LNP (designated LNPLH) with two different phase transitions near physiological conditions for delivering mRNA. A bicistronic mRNA encoding a single domain intracellular antibody fragment and green fluorescent protein (GFP) was introduced into a range of human cancer cell types using LNPLH, and the protein expression was measured via fluorescence corresponding to the GFP expression. The LNPLH/mRNA complex demonstrated low toxicity and high delivery, which was significantly enhanced when the transfection occurred in the presence of acoustic shock waves. The results suggest that the thermodynamic state of LNPs provides an important criterion for stimulus responsive fusogenic nanoparticles to deliver macrodrugs to the inside of cells.